"HISTORY AND EVOLUTION OF PUNCTUATION IN ENGLISH AND UZBEK: A COMPARATIVE ANALYSIS" (Modern education and development, 2025)
This article is dedicated to the comparative analysis of the historical development and modern punctuation rules in English and Uzbek languages. Various sources have been analyzed to reveal the significance of punctuation and its linguistic features.